Susceptibility of two karyotypic forms of Anopheles aconitus (Diptera: Culicidae) to Plasmodium falciparum and P. vivax - Junkum A. (2014)
Four laboratory-raised colonies of two karyotypic forms of Anopheles aconitus, i.e., Form B (Chiang Mai and Phet Buri strains) and C (Chiang Mai and Mae Hong Son strains), were experimentally infected with Plasmodium falciparum and P. vivax using an artificial membrane feeding technique and dissected eight and 12 days after feeding for oocyst and sporozoite rates, respectively. The results revealed that An. aconitus Form B and C were susceptible to P. falciparum and P. vivax, i.e., Form B (Chiang Mai and Phet Buri strains/P. falciparum and P. vivax) and Form C (Chiang Mai and Mae Hong Son strains/P. vivax). Comparative statistical analyses of the oocyst rates, average number of oocysts per infected midgut and sporozoite rates among all strains of An. aconitus Form B and C to the ingroup control vectors, An. minimus A and C, exhibited mostly no significant differences, confirming the high potential vector of the two Plasmodium species. The sporozoite-like crystals found in the median lobe of the salivary glands, which could be a misleading factor in the identification of true sporozoites in salivary glands were found in both An. aconitus Form B and C.